PENGEMBANGAN MEDIA PROMKES UNTUK PENCEGAHAN PENYAKIT JANTUNG KORONER DI RUMAH SAKIT dr. RASIDIN PADANG - Syafrawati Syafrawati; Shelvy Haria Roza (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2023)
Coronary Heart Disease (CHD) or cardiovascular disease is currently one of the main and first causes of death in developed and developing countries, including Indonesia. The prevalence of CHD in Indonesia, based on the estimated number of sexes, shows around 352,618 men and 442,674 women. Based on age, the highest prevalence is in the population aged 65-74 years (3.6%) which means that out of 100 people 3.6 suffer from CHD. Hospital Health Promotion (PKRS) is very important and necessary in prioritizing promotive and preventive efforts, so that all aspects of health services can be carried out in a comprehensive manner. The activities carried out were in the form of health promotion using the counseling method (delivering prepared material) using posters and pocket books on what coronary heart disease is, its symptoms, causes, good food for sufferers and forms of first aid for coronary heart sufferers. Before delivering the material, a pre-test was carried out and after the material was given a post-test. The target of the activity is patients in the cardiac polyclinic of dr. Rasidin Padang. After counseling there was a significant increase in patient knowledge about the material presented from an average of 60 to 75, or an increase in knowledge of 20%. It is suggested that hospitals can put posters in the hospital waiting rooms around health service polyclinics so that health information can be seen by patients at the hospital.